The effect of starter combination and types of milk against physicochemical characteristics of cow milk yoghurt - Erina Septianti; Wanti Dewayani; Riswita Syamsuri (Hasanuddin University Food Science and Technology Study Program, 2020)
Yoghurt was produced through the fermentation of bacteria Lactobacillus bulgaricus and Streptococcus thermophillus. In making yoghurt, various kinds of milk can be used such as: fresh milk, skim milk and full cream milk. The purpose of the study is to provide yoghurt in accordance with the right application of milk and yoghurt starter. The findings of research provide scientific information that useful for the technology development in the field of cow's milk processing industry. The study began with making starter, processing milk to be yoghurt and storing them in cold temperatures for four weeks. The study used a factorial Completely Randomized Design with three replications. The first factor is the number of starter/Lactic Acid Bacteria (e1 = Lactobacillus bulgaricus and Streptococcus thermophillus; e2 = combination of Lactobacillus bulgaricus, Streptococcus thermophillus, Bifidobacterium longum and Lactobacillus casei). The another factor is types of milk (s1 = fresh milk and s2 = skim milk). The parameter was discussed are physicochemical analysis including pH, protein, fat and lactose content. The results was showed the types of milk and the amount of starter used had a significant effect on fat content, protein content and lactose of the yoghurt produced did not match the pH value of yoghurt during storage at 4 weeks. The pH value obtained from fresh milk ingredients with a combination of 4 starters, a good level of yoghurt protein is produced from fresh milk ingredients with a combination of 2 starters, good fat content obtained from skim milk ingredients with a combination of 2 starters and fresh milk with a combination of 4 starters, while good lactose content in a combination of 2 starters both in fresh milk and skim milk.